2023
DOI: 10.3389/fimmu.2023.1216211
|View full text |Cite
|
Sign up to set email alerts
|

The genetic associations of COVID-19 on genitourinary symptoms

Abstract: BackgroundRecently emerged reports indicated that patients with coronavirus disease 2019 (COVID-19) might experience novo genitourinary symptoms after discharge. Nevertheless, the causal associations and underlying mechanisms remain largely unclear.MethodsGenome-wide association study (GWAS) statistics for COVID-19 and 28 genitourinary symptoms with consistent definitions were collected from the COVID‐19 Host Genetic Initiative, FinnGen, and UK Biobanks. Mendelian randomization (MR) analyses were applied to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…ROC analysis was employed to assess the diagnostic efficiency of diagnostic indicators, using the AUC value to select the top 20 diagnostic indicators, for which the R package ‘pROC’ was utilized. The ‘ggplot2’ package in R was used for graphical plotting, and Adobe Illustrator was employed for color and layout optimization, as previously described ( 21 ). For handling null and missing values, this study identified both using R, initially filling them using the mean value of each test item.…”
Section: Methodsmentioning
confidence: 99%
“…ROC analysis was employed to assess the diagnostic efficiency of diagnostic indicators, using the AUC value to select the top 20 diagnostic indicators, for which the R package ‘pROC’ was utilized. The ‘ggplot2’ package in R was used for graphical plotting, and Adobe Illustrator was employed for color and layout optimization, as previously described ( 21 ). For handling null and missing values, this study identified both using R, initially filling them using the mean value of each test item.…”
Section: Methodsmentioning
confidence: 99%
“…These procedures included restricting SNP missingness to <0.05 and ensuring a minor allele frequency (MAF) of >0.01 [ 19 ]. Additionally, akin to methodologies employed in previous studies, quality assessment can be gauged by examining the adherence to the three stated assumptions [ 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, confirming the genuine causal risk factors of kidney stones becomes a critical prerequisite for future disease prevention and treatment and strategies. The MR approach with genetic markers as an instrumental variable (IV) has been widely used to assess the causal relationships of the exposure on the outcome in epidemiology [10][11][12]. MR could not only minimize confounding by environmental factors as allelic genes are both randomly assigned and fixed during gamete formation and conception, but also overcome reverse causation bias as allelic randomization antedates the onset of disease.…”
Section: Introductionmentioning
confidence: 99%